2019
DOI: 10.1111/bjd.17528
|View full text |Cite
|
Sign up to set email alerts
|

Chronic urticaria and osteoporosis: a longitudinal, community‐based cohort study of 11 944 patients

Abstract: Background Chronic urticaria (CU) carries many risk factors for osteoporosis, but data on the relationships between CU and osteoporosis are lacking. Objectives To evaluate the association between CU and osteoporosis in a large community-based study. Methods A nationwide observational longitudinal cohort study was conducted. CU was defined as four pairs of urticaria diagnoses; each pair was recorded within a period of 6 weeks and was registered by physicians in a primary-care setting. Patients with CU and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In fact, in patients with OP and osteopenia, mast cells produce bone cytokines capable of directing remodeling towards bone loss [62]. In that study, it is shown that patients with CU have a higher rate of OP and hypocalcemia, as well as lower levels of parathyroid hormone (PTH) and vitamin D. In fact, the levels of PTH are significantly lower in patients with OP and CU, compared to patients diagnosed with OP alone [61,62]. In patients with CU, the presence of risk factors, which include female sex, exposure to systemic corticosteroids, changes in thyroid function, smoking, and obesity, increases the risk of OP [62].…”
Section: Urticariamentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in patients with OP and osteopenia, mast cells produce bone cytokines capable of directing remodeling towards bone loss [62]. In that study, it is shown that patients with CU have a higher rate of OP and hypocalcemia, as well as lower levels of parathyroid hormone (PTH) and vitamin D. In fact, the levels of PTH are significantly lower in patients with OP and CU, compared to patients diagnosed with OP alone [61,62]. In patients with CU, the presence of risk factors, which include female sex, exposure to systemic corticosteroids, changes in thyroid function, smoking, and obesity, increases the risk of OP [62].…”
Section: Urticariamentioning
confidence: 99%
“…Several pathogenetic mechanisms, including the dysregulation of intracellular signaling pathways in basophils and mast cells, an abnormal innate immunity response, and the simultaneous activation of inflammatory response and coagulation system, are involved [59,60]. In the active phase of CU, especially in the spontaneous form, increased circulating levels of inflammatory markers including interleukin IL-6, fibrin degradation products, D-dimer, and C-reactive protein (CRP) are found [61]. CU has been associated with a low-grade or persistent inflammation over time with an increase in inflammatory markers in relation to the severity of the disease.…”
Section: Urticariamentioning
confidence: 99%
“…Epidemiological evidence is reported on the association between chronic urticaria (CU) and osteoporosis [76]. CU as a low grade inflammatory condition [77][78][79] is a potential risk factor for osteoporosis, to which the female predisposition and the exposure to systemic corticosteroids is added.…”
Section: Chronic Urticariamentioning
confidence: 99%
“… 1 This chronic condition is associated with various co-morbidities, decreased quality of life, and reduced ability to maintain normal activities. 2 , 3 , 4 Two immune mechanisms were linked with CSU pathogenesis. “Type I″ response that is mediated by IgE antibodies, but unlike classic allergy, these IgE antibodies are directed at auto-antigens (e.g.…”
Section: Introductionmentioning
confidence: 99%